Intensive pulmonary rehabilitation in a pediatric lung transplantation patient: A case report. Issue 17 (30th April 2021) - Choi, Eun Jung; Kim, Won; Jeon, Jae Yong; Ko, Eun Jae; Yu, Jinho; Choi, Se Hoon; Lee, Seung Hak; Sung, In Young
Abstract: Background: The pediatric lung transplant is a very important treatment for patients with end-stage lung diseae, and pulmonary rehabilitation (PR) is also an important factor in determining the prognosis. However, there is no much literature available on pulmonary rehabilitation in pediatric patients' post lung transplant. Through this case report, we would like to present our intensive PR program for pediatric patients' post-lung transplant. Patient concerns: The 10-year-old boy's breathing before receiving a lung transplant continued to deteriorate and he eventually became dependent on a wheelchair. Diagnosis: He was diagnosed with infantile acute lymphoblastic leukemia at 6 months of age. At the age of one year, he underwent allogeneic bone marrow transplantation, but was diagnosed with post-transplantation bronchiolitis obliterans (PTBO) two months later. He had a lung transplant at the age of 10. Interventions: He was hospitalized and received an initial assessment. This assessment included functional, cognitive, and psychological evaluations. He additionally completed PR exercises twice daily for two weeks. After discharge, he continued to participate in an outpatient-based PR program for three months. During the outpatient phase, PR exercises were performed once weekly, in addition to home-based cognitive training. Outcomes: Our intensive post-lung PR program improved our patient's exercise capacity, lung function, and quality of life. As a comprehensive rehabilitation service, our program also included a cognitive training component. Conclusion: We describe an intensive PR program tailored to pediatric patients' post-lung transplant. The program was feasible and resulted in improvements in functional exercise capacity, lung function, and quality of life. Future research into our method is necessary for continued improvement of this novel program.